2007
DOI: 10.1038/sj.ijir.3901540
|View full text |Cite
|
Sign up to set email alerts
|

Physician perceptions of sexual dysfunction related to benign prostatic hyperplasia (BPH) symptoms and sexual side effects related to BPH medications

Abstract: In a large-scale epidemiology study, 50% of aging men reported erectile dysfunction (ED) or ejaculatory dysfunction (EjD), with lower urinary tract symptoms (LUTS) an independent risk factor for each of these conditions. In light of the shift from urologists (UROs) to primary care/ internal medicine physicians (PCPs) for the initial management of men with LUTS associated with benign prostatic hyperplasia (BPH), a survey was conducted to assess the perceptions of UROs and PCPs regarding sexual dysfunction (SD) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 36 publications
1
27
0
Order By: Relevance
“…The results of pilot studies [21,22] also showed positive effects of testosterone undecanoate therapy on LUTS in men with LOH. If indeed testosterone treatment improves Table I symptoms of LUTS, this would benefit patients since pharmacological treatment of LUTS (a1-adrenergic receptor antagonists and 5a-reductase inhibitors) often leads to sexual complaints [23]. And testosterone appears to have a wide range of effects in hypogonadal elderly men, such as on features of metabolic syndrome, mood, erectile function and anabolic effects on muscle and bone.…”
Section: Discussionmentioning
confidence: 98%
“…The results of pilot studies [21,22] also showed positive effects of testosterone undecanoate therapy on LUTS in men with LOH. If indeed testosterone treatment improves Table I symptoms of LUTS, this would benefit patients since pharmacological treatment of LUTS (a1-adrenergic receptor antagonists and 5a-reductase inhibitors) often leads to sexual complaints [23]. And testosterone appears to have a wide range of effects in hypogonadal elderly men, such as on features of metabolic syndrome, mood, erectile function and anabolic effects on muscle and bone.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, IPSS has no ability to identify symptoms related to erectile dysfunction. Recently, a survey revealed that physicians underestimate the prevalence of sexual dysfunction in men with LUTS/BPH [32]. Urologists should inquire about possible coexistence of erectile dysfunction in men seeking treatment for LUTS.…”
Section: A Rising Questionmentioning
confidence: 99%
“…Several studies have examined the practice patterns of PCPs in the management of BPH and indicate that a signifi cant percentage were not following published guidelines prior to the most recent AUA guidelines, differing from urologists [36][37][38]. This discrepancy continued after the release of the AUA guidelines, with urologists being twice as likely to use AUASI (81% to 41%) as part of their initial evaluation [39,40].…”
Section: Physician Practice Patternsmentioning
confidence: 97%